Extensive study of optical contrast between bulk and nanoscale transition metal dichalcogenide semiconductors. (August 2021) - Parmar, Ankush; Kaur, Jashangeet; Sharma, Manish Dev; Goyal, Navdeep
Abstract: A remarkable refinement in the optical behavior of two-dimensional transition metal dichalcogenides (TMDs) has been brought to light when cleaved from their respective bulks. These atomically thin direct bandgap semiconductors are highly responsive to optical energy which proposes the route for futuristic photonic devices. In this manuscript, we have substantially focused on the optical study of MoS2 and WS2 nanosheets and comparative analysis with their bulk counterparts. The synthesis of nanosheets has been accomplished with liquid exfoliation followed by fabrication of thin films with drop-casting technique. X-ray diffraction and field emission scanning electron microscopy affirmed the morphology, whereas, UV–visible spectroscopy served as the primary tool for optical analysis. It was observed that several parameters, like optical conductivity, optical band-gap energy etc. have enhanced statistics in the case of exfoliated nanosheets as compared to their respective bulks. Some researchers have touched upon this analysis for MoS2, but it is completely novel for WS2 . We expect our work to clearly distinguish between the optical behaviors of nanoscale and bulk TMDs so as to intensify and strengthen the research related to 2D-layered materials for optoelectronic and photovoltaic applications.